Yu Ping Feng San Exert Anti-Angiogenesis Effects through the Inhibition of TSLP-STAT3 Signaling Pathways in Hepatocellular Carcinoma - Yuan, Qin (Evid Based Complement Alternat Med, 2019)
BACKGROUND: Clinically, Yu ping feng san (YPFS) has been extensively used as a medication for treating immune deficiency, and YPFS is combined with chemotherapy drugs to treat cancer, including hepatocellular carcinoma (HCC), lung cancer, and pancreatic cancer. Previous research has shown that YPFS has a therapeutic effect on HCC by improving the immunosuppressive state of the liver cancer microenvironment. The present study aimed to investigate the effect of YPFS on angiogenesis of HCC. METHODS: High-performance liquid chromatography (HPLC) was used to certify the composition of YPFS. An orthotopic transplanted model of murine HCC was entrenched. Immunohistochemistry was used to observe the changes of the microvessel density (MVD). The MTT assay was used to detect the cell viability. ELISA was performed to analyze the expression of related factors. Western blot was used to analyze the protein expression. Tube formation assay was used to analyze the anti-angiogenic efficiency. RESULTS: YPFS significantly reduced the tumor volume and weight, thus exerted the growth inhibitory effect. The level of MVD and VEGF was obviously decreased in YPFS-treated HCC-bearing mice, and the YPFS treatment also reduced the VEGF level in Hepa1-6 cells. Further study revealed that the expression of TSLP/TSLPR and p-STAT3/STAT3 was decreased by YPFS. The level of MVD and VEGF and the expression of TSLP/TSLPR and p-STAT3/STAT3 in tumor tissue and Hepa1-6 cells were suppressed by incubation with the anti-TSLP antibody, whereas treatment with the anti-TSLP antibody in YPFS-treated cells did not cause further significant inhibition compared with the cells treated only with YPFS. More importantly, YPFS inhibited proliferation, expression of p-STAT3/STAT3, and tube formation of HUVECs induced by TSLP. CONCLUSIONS: These results indicated that YPFS attenuated the activation of the TSLP-STAT3 signaling pathway by inhibiting the immune-related factor-TSLP, thereby inhibiting the formation of hepatic microvessels and exerting an anti-HCC effect.